Impactos ambientais da pedreira no município de Caraúbas-RN - Lopes, Jessica Rafaelly Almeida (Universidade Federal Rural do Semi-Árido, 2017)
The mining is a propulsive activity of the economic development of the country, as well in the touching to social factors, once that is significant source of employment and income; however, resuling in significative impacts to envinromental, affecting the physical, biotic and anthropic environment, these impacts can have beneficial and adverse character. Thereby, it was aimed to identify the main environmental impacts caused by quarry localized in the county of Caraúbas – RN. The search was accompleshed by means of a case study. The methodology consists in two stages, the first one together to population that lives in the area of the surroundings of the quarry, in that was applied 88 questionnaires, with the intent of detecting the envinromental impacts caused by mineral extraction in the region. In the second stage, it was applied 13 questionnaires together to employees, in a way to evaluate the impacts sensed by workers of the enterprise. Still in the scope, it was elaborated quantitative and qualitative matrices for helping in the identification of the impacts genered by activity in question. As results, among the various identified impacts, those who most stood out were vibrations and noises, with 19,32% and 7,95%, respectively. Stand out yet the problems caused by detonations and explosions coming of the mining activity because in 53,41% of the residences sampled present some kind of damage the its structures. Being that the impacts sensed are contributing directly for the damage in the structure of the residences and the water reservoirs (split and cracks). Besides that, it was verified that 92,31% of the employees think good the security in the enterprise, what contributes for the development of its activities. However, it was found that 23,08% already suffered some kind of work accidente. Thus, it can claim that the mining activity brings social and environmental consequences, such as: noises, vibrations, discomfort and structure damages, and that its execution cause significant impact to environmental.
Keywords: Meio Ambiente; Environmental; Mineração; Mining; Impacto Ambiental; Environmental Impact; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA